USP5‐Rich Apoptotic Extracellular Vesicles Regulate Nucleus Pulposus Cells Apoptosis and DNA Damage Repair by Preventing E2F1 Proteasomal Degradation - Pengzhi Shi; Haiyang Gao; Zhangrong Cheng; Wenbo Wu; Anran Zhang; Xianglong Chen; Wang Wu; Yukun Zhang (Journal of Extracellular Vesicles)
ABSTRACT Mesenchymal stem cell (MSC) transplantation is considered one of the most promising regenerative strategies for treating degenerative musculoskeletal diseases, yet its underlying therapeutic mechanisms remain incompletely understood. In this study, we demonstrate that transplanted MSCs regulate apoptosis and DNA damage repair (DDR) in senescent nucleus pulposus cells (NPCs) by releasing apoptotic extracellular vesicles (ApoEVs), thereby delaying the process of intervertebral disc degeneration (IVDD). Mechanistically, we found that NPCs in degenerated discs exhibit abnormal subcellular localization of the deubiquitinase ubiquitin specific peptidase 5 (USP5), with excessive cytoplasmic retention leading to aberrant ubiquitination and degradation of the E2F transcription factor 1 (E2F1). Following transplantation into the degenerative disc microenvironment, MSCs undergo extensive apoptosis in the short‐term and release ApoEVs enriched in highly acetylated USP5. These vesicles promote nuclear translocation of USP5 in NPCs, which stabilizes E2F1 by preventing its ubiquitin‐mediated degradation. This cascade reduces DNA damage and apoptosis in NPCs and enhances their functional activity. Overall, our findings reveal a previously unrecognized mechanism by which apoptotic donor MSCs exert therapeutic effects through intercellular communication, specifically by modulating recipient NPCs apoptosis and DDR pathways. This study underscores the critical role of donor cell apoptosis in the therapeutic efficacy of stem cell transplantation and provides new insights for optimizing regenerative medicine strategies.